The immunity function of rodlet cells in the intestine of Binni fish (Mesopotamichthys sharpeyi) - Karim, Abdulkarim Jafar; Hassan, Ali Hussein; Kadhim, Khalid Hadi; Kadhim, Khalid Kamil (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Rodlet cells produce secretions of glycoproteins in nature. This study investigated the microscopic morphology, histochemical and immunohistochemical reactions, and distribution of the rodlet cells in the gut of Binni fish (Mesopotamichthys sharpeyi). Materials and Methods: Thirty samples were obtained from the cranial, middle, and caudal portions of Binni intestine immediately after being euthanized, fixed in Bouin’s solution for 18 h at 24°C, and had undergone routine histological processing, different conventional histochemical stains, and immunostaining with TNF-α and S100 protein antibody. Results: The intestine of Binni fish showed different stages of rodlet cells classified into three distinctive forms: vesicular, granular, and mature cells. Rodlet cells are poorly stained with hematoxylin and eosin. Their secretory granules have a weak positive reaction with periodic acid-Schiff (PAS) and Alcian blue (AB), and react positively to combined AB and PAS. Rodlet cells were stained lightly with Safranin O, observed pink in color by Giemsa stain, and showed reactivity to Masson’s and Mallory trichrome stains. Rodlet cells were immunostained positively against TNF-α and S100 antibodies, indicating that they have an immune function. Conclusions: Rodlet cells, with their neutral glycoprotein secretions, play a crucial role in the immunity of Binni fish intestine. J. Adv. Vet. Anim. Res., 9(2): 282–289, June 2022 http://doi.org/10.5455/javar.2022.i594